Role of BCLAF‐1 in PD‐L1 stabilization in response to ionizing irradiation. Issue 10 (2nd August 2021) - Ma, Zhao; Wang, Han; Meng, Fanbiao; Han, Yamei; Chen, Yefei; Xiao, Mingming; Jiang, Hongjing; Yu, Zhentao; Xu, Bo
Abstract: Programmed cell death ligand 1 (PD‐L1) is a major immunosuppressive checkpoint protein expressed by tumor cells to subvert anticancer immunity. Recent studies have shown that ionizing radiation (IR) upregulates the expression of PD‐L1 in tumor cells. However, whether an IR‐induced DNA damage response (DDR) directly regulates PD‐L1 expression and the functional significance of its upregulation are not fully understood. Here, we show that IR‐induced upregulation of PD‐L1 expression proceeds through both transcriptional and post‐translational mechanisms. Upregulated PD‐L1 was predominantly present on the cell membrane, resulting in T‐cell apoptosis in a co‐culture system. Using mass spectrometry, we identified PD‐L1 interacting proteins and found that BCLAF1 (Bcl2 associated transcription factor 1) is an important regulator of PD‐L1 in response to IR. BCLAF1 depletion decreased PD‐L1 expression by promoting the ubiquitination of PD‐L1. In addition, we show that CMTM6 is upregulated in response to IR and participates in BCLAF1‐dependent PD‐L1 upregulation. Finally, we demonstrated that the ATM/BCLAF1/PD‐L1 axis regulated PD‐L1 stabilization in response to IR. Together, our findings reveal a novel regulatory mechanism of PD‐L1 expression in the DDR. Abstract : IR‐induced PD‐L1 upregulation expression proceeded through post‐translational mechanisms. We identified BCLAF1 as a new PD‐L1 stabilization regulator in response to IR.